NORM CHARACTERISTICS OF ISLAMIC BANKING IN INDONESIA ON MURABAHAH INSTRUMENT TOWARDS BEYOND BANKING - Nurjannah S; Hilman Syahrial Haq; Khudzaifah Dimyati; Bambang Setiaji (Jurnal IUS Kajian Hukum dan Keadilan, 2018)
The dynamics of Islamic banking since 2008 has grown rapidly after the enactment of Law Number 21 Year 2008 concerning Islamic Banking. Murabahah products undergo several stages of review or assessment in order to achieve compatibility between the fundamental aspects of its welfare and operations. The existence of various perceptions and implementations so far has become an important issue to be studied, considering the standardization of technical product which is a minimum standard, required as a reference for implementation products. This study used a type of doctrinal research, with textual inference procedures and qualitative descriptive analysis. The presents of Sharia or Islamic issues, legal issues and operational issues are several characteristics of norms stated in the Islamic Banking Law regarding murabahah instrument. Standard Book of murabahah products based on the Financial Services Authority Regulation which contains the capacity and service standards that are derived from important norms and guidelines in the operation of murabahah instrument. Understanding and implementing the Islamic banking industry brings together two dimensions of value, that are the value of professionals in the financial world and the value of compliance with sharia principles, one of which is the rules of commercial transaction that are not mixed with the rules of credit. These fundamental indicators determine the norm characteristics of Islamic banking in Indonesia. Thus, the construction of legal reforms for Islamic banks as beyond banking is well realized.